Functional motor performance and reliability of the Dubousset Functional Test in ambulatory children with spastic cerebral palsy - Ergun, Betul; Baykan, Muge; Copuroglu, Ozge Baykan; Abakay, Hanife; Guc, Ayse; Karabulut, Ridvan (Taylor & Francis Inc, 2026)
BackgroundCerebral palsy (CP) causes permanent motor impairments, limiting postural control and mobility. The Dubousset Functional Test (DFT) was developed to assess daily activity performance, but its reliability and validity in pediatric CP are unclear. This study aimed to evaluate its reliability, convergent and discriminative validity, and clinical utility in children with spastic CP at GMFCS Levels I - II. MethodsThirty-three children aged 6-15 years with spastic CP (GMFCS I - II) participated in this cross-sectional methodological study. The DFT (Rise-and-Walk, Step, Sit-to-Stand, and Dual Task subtests) was administered along with the Timed Up and Go (TUG), Dual-task TUG, 3-Meter Backward Walk Test (3MBWT), Functional Reach Test (FRT), and Pediatric Balance Scale (PBS). All assessments were conducted twice, seven days apart, by a single experienced physiotherapist. ResultsThe DFT demonstrated excellent reliability, with ICC(3,2) values ranging from 0.91 to 0.95 and minimal measurement bias (-0.61 to 0.36 s). The smallest detectable change (SDC) ranged from 2.1 to 13.0 s, confirming high measurement precision. Strong correlations were observed between the DFT Dual Task and both TUG (r = 0.95, p < .001) and Dual-task TUG (r = 0.95, p < .001), supporting convergent validity. ROC analysis indicated excellent discriminative accuracy for identifying children with balance limitations (PBS < 45) (AUC = 0.82, sensitivity = 0.81, specificity = 0.78). ConclusionThe DFT is a reliable, valid, and clinically feasible tool for assessing balance and mobility in ambulatory children with spastic CP at GMFCS I - II, supporting routine rehabilitation use. Trial RegistrationClinicalTrials.gov (NCT06831591).
Keywords: Cerebral palsy; Dubousset Functional Test; Gross Motor Function; rehabilitation; reliability